Factors affecting enterprise resource planning migration: the South African customer’s perspective - Mushayi, Precious R (My University, 2021)
Enterprise resource planning (ERP) systems are a crucial and strategic component of most organisations’ information systems (IS). The advent of the digital economy has pushed traditional ERPs to evolve into intelligent ERP systems that are built to integrate with smart technologies such as artificial intelligence and machine learning. There is a need to understand how the digital economy has affected the design of ERP systems and how customers in developing countries are adapting to these changes. The purpose of this study was to identify the factors that influence the decisions of ERP customers in developing countries on whether to adopt intelligent ERP technologies such as SAP S/4 HANA. The technological-organisational-environmental and institutional theory frameworks were used as the foundation upon which the factors that influence intelligent ERP adoption were studied. The study focused on adopters and non-adopters of SAP S/4 HANA in the South African context. Guided by the positivist paradigm, a questionnaire-based survey was developed using theoretical constructs from existing studies of technology adoption and distributed to a sample of 95 companies, which were selected through purposive sampling. Nine factors were hypothesised to have an impact on intelligent ERP adoption, namely information, communication and technological (ICT) infrastructure, the availability of cyber-security systems, technical skills, organisational size, top management support, coercive pressures, mimetic pressures, normative forces and governmental regulations. Based on the responses received from 84 organisations, four factors out of the nine initial factors were found to have a significant impact on intelligent ERP migration, namely ICT infrastructure, the availability of cyber-security systems, mimetic forces ,and normative pressures. This study may be useful to ERP vendors with customers in developing countries, to understand existing and potential customer perceptions of intelligent ERPs. It will also give insight to academics who seek to build on their understanding of technology adoption in developing countries, especially in this era of digital transformation.
A research report submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand in partial fulfilment of the requirements for the degree of Master of Commerce (in the field of Information Systems), 2021
Keywords: Intelligent ERP; Migration; Adoption TOE; Institutional Theory; Digital Transformation